Bicycles, 'Barrows, and Donkeys: Pinning a Tale on the Irish Border. Issue 2 (3rd April 2018) - Leary, Peter
Abstract: A popular smuggling story still told in Ireland concerns a man who crossed the border every day, either on a bicycle or wheeling a wheelbarrow, and usually carrying some sort of load; hay, turf, potatoes, or vegetables—goods that were free from customs duty. The suspicious officials subjected the traveller to regular searches but could never catch him out. This article contextualizes that story in the history of the Irish border during the mid twentieth century, and locates it within Irish folklore traditions, before exploring its probable origin in similar tales found outside Ireland.